2016
DOI: 10.21053/ceo.2015.01648
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Antioxidative Enzyme Capacity in Tongue of Fischer 344 Rats

Abstract: ObjectivesAntioxidative enzyme efficiency changes in some organs with age. However, no study has been conducted on age-related antioxidant enzyme changes in tongue. In the present study, the authors investigated the activities of four antioxidative enzymes and their protein expressions in the tongues of young and old Fischer 344 rats.MethodsAge-dependent changes in the enzyme activities of total superoxide dismutase (SOD), Mn-SOD, Cu/Zn-SOD, catalase (CAT), and glutathione peroxidase (GPx) were determined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…In the present study, Western blotting showed that Nrf2 expression was suppressed in the tongue tissues of aged rats, which is in-line with our previous observation that antioxidant enzyme levels were diminished in aged rat tongues [ 5 ]. Smith et al [ 14 ] focused on miRNA-146a, the expression of which leads to age-associated reductions in Nrf2 expression.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, Western blotting showed that Nrf2 expression was suppressed in the tongue tissues of aged rats, which is in-line with our previous observation that antioxidant enzyme levels were diminished in aged rat tongues [ 5 ]. Smith et al [ 14 ] focused on miRNA-146a, the expression of which leads to age-associated reductions in Nrf2 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Further studies are needed to assess whether aged tongue tissues are prone to certain mitochondrial DNA mutations and to identify the factors that contribute to such mutations. In the present study, ROS were found to be up-regulated in an aged rat tongues, and based on our previous finding that antioxidant enzyme levels were reduced in aged rat tongues [ 5 ], we suggest the up-regulation of ROS was possibly caused by diminished antioxidant enzyme levels.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…8 In addition, persistent oxidative stress plays a key role in the pathogenesis and complications of diabetes. 11 Leptin is a hormone that is encoded by the leptin gene and secreted by adipocytes to regulate energy metabolism homoeostasis. For example, a previous study demonstrated that the activities of total superoxide dismutase (SOD), glutathione peroxidase (GPx) and copper/zinc (Cu/Zn) SOD are significantly lower on the tongues of aged rats compared with young rats, and the antioxidant defence system of aged rats is significantly declined.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous study demonstrated that the activities of total superoxide dismutase (SOD), glutathione peroxidase (GPx) and copper/zinc (Cu/Zn) SOD are significantly lower on the tongues of aged rats compared with young rats, and the antioxidant defence system of aged rats is significantly declined. 11 Leptin is a hormone that is encoded by the leptin gene and secreted by adipocytes to regulate energy metabolism homoeostasis. Once secreted into the circulation, it binds to the leptin receptor in the hypothalamus to function as an anorexigenic agent and promote energy consumption.…”
Section: Introductionmentioning
confidence: 99%